Repurposing population genetics data to discern genomic architecture: A case study of linkage cohort detection in mountain pine beetle (Dendroctonus ponderosae) - Trevoy, Stephan A.L.; Janes, Jasmine K.; Muirhead, Kevin; Sperling, Felix A.H. (John Wiley & Sons, Inc., 2019)
This article was originally published as: Trevoy, S.A.L., Janes, J.K., Muirhead, K., & Sperling, F.A.H. (2019). Repurposing population genetics data to discern genomic architecture: A case study of linkage cohort detection in mountain pine beetle (Dendroctonus ponderosae). Ecology and Evolution, 9(3), 1147-1159. https://doi.org/10.1002/ece3.4803 Genetic surveys of the population structure of species can be used as resources for exploring their genomic architecture. By adjusting filtering assumptions, genomewide single‐nucleotide polymorphism (SNP) datasets can be reused to give new insights into the genetic basis of divergence and speciation without targeted resampling of specimens. Filtering only for missing data and minor allele frequency, we used a combination of principal components analysis and linkage disequilibrium network analysis to distinguish three cohorts of variable SNPs in the mountain pine beetle in western Canada, including one that was sex‐linked and one that was geographically associated. These marker cohorts indicate genomically localized differentiation, and their detection demonstrates an accessible and intuitive method for discovering potential islands of genomic divergence without a priori knowledge of a species’ genomic architecture. Thus, this method has utility for directly addressing the genomic architecture of species and generating new hypotheses for functional research. https://viurrspace.ca/bitstream/handle/10613/26916/JanesEE2019.pdf?sequence=3 Alberta Agriculture and Forestry; Natural Resources Canada ‐ Canadian Forest Service; Northwest Territories Environment and Natural Resources; Manitoba Conservation and Water Stewardship; Ministry of Natural Resources and Forestry; Saskatchewan Ministry of Environment; Natural Science and Engineering Research Council of Canada, Grant/Award Number: NET GP 434810-12; Foothills Research Institute; Weyerhaeuser Company; West Fraser Timber Co. Ltd; Laval University; University of Alberta